Analysis of the Role of Karang Tinggi District as a Growth Center District in Central Bengkulu Regency in 2020 - Cikit Apriyanti; Handoko Hadiyanto; Edy Rahmantyo Tarsilohadi (Penerbit Jurnal Indonesia, 2021)
The objective of this study is to know of karang tinggi sub-disctric as a growth center of Bengkulu tengah in in encouraging economic growth in the district of Bengkulu Tengah and identifying which sub-districts can be used as supporters of growth centers and leading commodities in supporting the economy in Karang Tinggi sub-district. The analytical tools used in this research are Likert scale, gravity analysis and location quentient (LQ) analysis. Based on the Likert scale analysis, it is known that the Karang Tinggi sub-district has played a fairly good role as a growth center with a score of 2.96, because the availability of facilities owned by the Karang Tinggi sub-district is felt to be quite adequate and quite helpful in supporting all community activities both in economic, social activities. as well as government. The results show the gravity index analysis of sub-district that has the strongest interaction with Karang Tinggi sub-district is Talang Empat sub-district with a gravity index value of 7177051, followed by Taba Penanjung with a gravity value of 6005503 and Pondok Kelapa sub-district with a gravity index value of 5280297. The results obtained from the LQ analysis show that the leading commodities of the food crop subsector are corn, sweet potato and peanuts. Meanwhile, the plantation sub-sectors are oil palm, rubber and coffee.